Waqf reporting to fulfil stakeholder attribution in Waqf islamic councils / Dalila Daud, Rashidah Abdul Rahman and Zaluddin Sulaiman - Daud, Dalila; Abdul Rahman, Rashidah; Sulaiman, Zaluddin (Institute of Business Excellent (IBE), 2011)
This article discusses the limitations of current theories of arguments which prove not suitable to waqf institute. This articles also redefining specifications of stakeholder theory to fulfill the waqf requirement. A conceptual model of 3ts based on Tawhidic approach is uniquely derived from the basic concept of Muslim responsibility and accountability to Allah. The model identifies the important parties so that adequate and reliable information can identify the suitable reporting among these groups. The current paper integrates accountability theory with stakeholder theory to examine whether the council is performing and fulfilling the intention of interested parties, whilst introducing the “triple accountability” in order to meet the demand of reporting to stakeholders. This article is in different cultural settings, a globally acceptable model is offered, and it draws on and completes existing managerial and some guidelines for the reporting for best practice of waqf governance. This paper also designs solutions through “waqf stakeholder model” which can lead to better guidelines for traditional and contemporary waqf activities (information, interaction, et al.) towards more holistic solution.